Development of a Genus-Universal Nucleotide Signature for the Identification and Supervision of Ephedra-Containing Products - Gang Wang; Xuanjiao Bai; Xiaochen Chen; Ying Ren; Jianping Han (Molecules, 2022)
Ephedra plants generally contain ephedrine alkaloids, which are the critical precursor compounds of methamphetamine (METH). METH could cause serious physical and mental damage, and therefore Ephedra materials are strictly in supervision internationally. However, unlawful utilization of Ephedra herbs and its products still exist. Thus, it is imperative to establish a universal method for monitoring Ephedra ingredients in complex mixtures and processed products. In this study, 224 ITS2 sequences representing 59 taxa within Ephedra were collected, and a 23-bp genus-level nucleotide signature (GTCCGGTCCGCCTCGGCGGTGCG) was developed for the identification of the whole genus. The specific primers MH-1F/1R were designed, and 125 individuals of twelve Ephedra species/varieties were gathered for applicability verification of the nucleotide signature. Additionally, seven batches of Chinese patent medicines containing Ephedra herbs were used to test the application of the nucleotide signature in complex and highly processed materials. The results demonstrated that the 23-bp molecular marker was unique to Ephedra and conserved within the genus. It can be successfully utilized for the detection of Ephedra components in complex preparations and processed products with severe DNA degradation. The method developed in this study could undoubtedly serve as a strong support for the supervision of illegal circulation of Ephedra-containing products.